Integrating Sheep Grazing into Cereal‐Based Crop Rotations: Spring Wheat Yields and Weed Communities. (1st January 2015) - Miller, Zach J.; Menalled, Fabian D.; Sainju, Upendra M.; Lenssen, Andrew W.; Hatfield, Patrick G.
Abstract : Crop diversification and integration of livestock into cropping systems may improve the economic and environmental sustainability of agricultural systems. However, few studies have examined the integration of these practices in the semiarid areas of the Northern Great Plains (NGP). A 3‐yr experiment was conducted near Bozeman, MT, to compare the effects of crop rotation diversity and weed management practices imposed during fallow periods [sheep ( Ovis aries ) grazing, reduced tillage, and conventional tillage] on spring wheat ( Triticum aestivum L.) yields and weed pressure. Management treatments were applied to replicated whole plots, within which the split‐plots received crop rotation treatments [continuous spring wheat (CSW) and a 3‐yr rotation of annual forage, fallow, and spring wheat, where each phase was present in each year]. In the initial 2 yr, the realized rotational treatments were wheat–fallow and CSW. In the final year, wheat was grown following all phases of the diversified rotation. Yields were similar among management treatments within the wheat–fallow and CSW rotations. Weed pressure was generally low but perennial weeds were more abundant in grazing‐managed, wheat–fallow systems. The integration of livestock into the annual hay crop–fallow–spring wheat rotation was associated with a nearly 30‐fold increase in weed pressure and a yield reduction of 51.2% compared to conventional management. The results suggest that although targeted sheep grazing is a viable alternative to conventional fallow management in CSW and wheat–fallow rotations, successful integration of livestock in diversified cropping systems requires more effective weed management practices.